Introduction to basic medical sciences: anatomy, biochemistry, physiology, microbiology, parasitology, pathology and pharmacology - Syed Ahmad, Pakeer Oothuman (IIUM Press, International Islamic University Malaysia, 2018)
This book offers a ‘peek’ overview of the subjects in first two years in most medical and health related programmes. Herein is a collection of simple introductions to the major disciplines in basic medical sciences such as anatomy (embryology, histology), biochemistry, physiology, microbiology, parasitology, pathology and pharmacology. Students who are in their Matriculation years, Form 5, Form 6 or A Levels (biology major) who wish to pursue a programme in medicine, dentistry, pharmacy, nursing or any of the health related programme can benefit from reading these introductory chapters, and also decide if this is the field they wish to study. They will know what they are getting into. This is the main aim of this book. Students who have already entered a medical/ health programme can better prepare themselves for the preclinical years. Diagrams and cartoons are meant to help understand the content and amuse the readers.